The productive potential and limits of landscape conflicts in light of Ralf Dahrendorf’s conflict theory - Kühne, Olaf; Weber, Florian; Berr, Karsten (SocietàMutamentoPolitica, 2019)
Ralf Dahrendorf’s conflict theory posits social conflict as, under certain circumstances, productive. Working from a constructivist view of language, we ask to what extent this applies to the conflicts currently arising around the social construct of «landscape», either from different interpretations of that concept or from different evaluations of the physical manifestations of human activity to which it refers. Are such conflicts socially productive? How can they become so? Our theoretical premises are clarified in a review of recent empirical inquiries into the German energy transition, a national undertaking which – following the political decision to exit nuclear-powered energy production by 2022 – has turned into a central field of social conflict, due to the ensuing massive growth not only of alternative power plants but also of electricity transmission networks. Regarding controversy in this context as normal, and eschewing simple solutions, we argue for the importance of recognizing opposing interests as legitimate, not categorizing opposition as per se immoral, agreeing rules of procedure, and accepting decisions that abide by those rules. Conclusions are drawn for both theory and practice.